PENGARUH PEMBERIAN PUPUK BOKASHI YANG BERBEDA TERHADAP KANDUNGAN PROTEIN DAN SERAT KASAR RUMPUT GAJAH (Pennisetum purpureum ) - Tintin Rostini; Gusti Khairun Ni'mah; Sosilawati Sosilawati (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2016)
The availability of quality forage is limited so that the necessary efforts to provide forage quality and its availability guaranteed. The aim of this study was to determine the effect of different Bokashi fertilizer on protein and crude fiber content of grass (Pennisetum purpureum). This research method using a completely randomized design (CRD) with 4 treatments and 5 replications consisting of: P0: Control (without Bokashi). P1: Giving ground bokasi 5 kg + 15 kg (ratio 1: 3). P2: Giving ground bokasi 10 kg + 10 kg (ratio 1: 1). P3: Giving bokasi 15 kg + 5 kg soil (3: 1) . observed. production of dry metter ingredients, protein and crude fiber from grass harvested at 60 days. The results showed that administration of different Bokashi can give effect to increase the protein content and decreased crude fiber. Concluded Bokhasi grass can improve the productivity of grass.